Interaksi Berbasis Gestur: Inovasi dalam Pengalaman Pengguna di Lingkungan Virtual - Gading, Rafli Arya; Akbar, Mukhamad Rizky; Nasution, Mansalwa Utama (Madani: Jurnal Ilmiah Multidisiplin, 2025)
This study discusses the evolution of human-computer interaction (HCI), which continues to advance alongside technological developments, particularly through innovations in gesture-based interaction. The research aims to explore the effectiveness of gestures in enhancing user experience in virtual environments, such as augmented reality (AR) and virtual reality (VR). The methodology employed is thematic analysis of relevant literature to identify innovation patterns and concept developments. Research findings indicate that: (1) gesture-based interaction improves user speed and accuracy in task completion; (2) the use of gestures creates a more immersive and intuitive experience; and (3) this technology enhances user engagement with digital systems, strengthening non-verbal communication. This research contributes significantly to the development of interface design and applications across various sectors, including education, entertainment, and healthcare.